2008
DOI: 10.1177/0093854807311719
|View full text |Cite
|
Sign up to set email alerts
|

Violent Video Games and Aggression

Abstract: Two studies examined the relationship between exposure to violent video games and aggression or violence in the laboratory and in real life. Study 1 participants were either randomized or allowed to choose to play a violent or nonviolent game. Although males were more aggressive than females, neither randomized exposure to violent-video-game conditions nor previous real-life exposure to violent video games caused any differences in aggression. Study 2 examined correlations between trait aggression, violent cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(74 citation statements)
references
References 30 publications
7
64
0
3
Order By: Relevance
“…Carers’ own explanations for any association between aggression seen in the media and children’s aggression (aggressive predisposition, “copying” negative role models, reinforcement of real-life aggression, desensitisation, being “hyper” after watching TV or playing video games) appear to be consistent with theories such as social learning theory, the cognitive neo-association model, social information-processing model and arousal theory [30-33]. But their suggested role of virtual aggression i.e., only additional to children’s aggressive predisposition, pre-existing behavioural problems and secondary to aggression seen in real-life, coheres with the more recently proposed “catalyst” model [34]. This model suggests that severe forms of aggression results from a combination of genetic and proximal environmental influences (family and peers), with distal environmental factors such as the media having a less important role of modelling the form of aggressive behaviour.…”
Section: Discussionsupporting
confidence: 72%
“…Carers’ own explanations for any association between aggression seen in the media and children’s aggression (aggressive predisposition, “copying” negative role models, reinforcement of real-life aggression, desensitisation, being “hyper” after watching TV or playing video games) appear to be consistent with theories such as social learning theory, the cognitive neo-association model, social information-processing model and arousal theory [30-33]. But their suggested role of virtual aggression i.e., only additional to children’s aggressive predisposition, pre-existing behavioural problems and secondary to aggression seen in real-life, coheres with the more recently proposed “catalyst” model [34]. This model suggests that severe forms of aggression results from a combination of genetic and proximal environmental influences (family and peers), with distal environmental factors such as the media having a less important role of modelling the form of aggressive behaviour.…”
Section: Discussionsupporting
confidence: 72%
“…Some studies found no association between violent video game play and aggressive reactions (e.g., Elson, Breuer, Van Looy, Kneer, & Quandt, 2014;Ferguson et al, 2008) while others found and still "believe" in negative effects of violent video game playing (Arriaga et al, 2015;Ellithorpe, Cruz, Velez, Ewoldsen, & Bogert, 2015).…”
Section: Discussion About Violent Video Games and Research Questionsmentioning
confidence: 99%
“…Erkekler, kızlara göre daha fazla şiddet içerikli oyunlara yöneldiklerinden, etkilenme dereceleri de cinsiyet temelinde farklılaşmaktadır. Elde edilen bulgular Anderson(2001) , Ferguson (2008 ve Kıran (2011)'ın araştırmaları ile uygunluk göstermektedir. Ancak bu oyunların şiddet öğeleri üzerinden kurgulandığı bilinmektedir.…”
Section: Sonuç Ve Tartışmaunclassified